The economics of social policy - Rosner, Peter (Cheltenham, UK ; Northampton, MA, USA : E. Elgar, 2003)
This book demonstrates how instruments of economics can be usefully employed to analyse social policy. The merits and limits of social policy programmes are discussed as answers to problems of market societies. The author addresses such key issues as access to health services, pension programmes, unemployment, poverty and family support.
Includes bibliographical references and index.
rpm 13/06/13
Loans
Keywords: Social policy -- Economic aspects